Mastectomy with immediate breast reconstruction: Results of a mono-centric 4-years cohort. (January 2021) - Quilichini, Olivia; Barrou, Julien; Bannier, Marie; Rua, Sandrine; Van Troy, Aurore; Sabiani, Laura; Lambaudie, Eric; Cohen, Monique; Houvenaeghel, Gilles
Abstract: Introduction: Oncological safety, quality of life and cosmetic outcomes seems to be similar between breast conserving surgery (BCS) and mastectomy with immediate breast reconstruction (IBR). We report our experience of IBR for consecutive mastectomies realized in a recent period of four years in order to determined immediate surgical results according to type of mastectomy and type of reconstruction, as mains objectives. Methods: All mastectomies with IBR during years 2016–2019 were included. A retrospective analysis with prospective data collection was performed. Results: We analyzed 748 IBR: 353 nipple-sparing mastectomies (NSM), 391 skin-sparing mastectomies (SSM) and 4 standard mastectomies, 551 with definitive implant or expanders and 196 with latissimus dorsi-flap (LDF). More NSM were performed during the 2 last years and more LDF were performed for high BMI, high breast cup-size, neo-adjuvant chemotherapy and radiotherapy and local recurrence. We realized 111 robotic NSM and 125 robotic LDF. Longer duration of surgery was significantly associated with the robotic procedures. The overall complications crude rate was 31.4% with 9.9% of re-operations and 5.8% of implant loss. Grade 2–3 complications were significantly associated with smoking. Breast complications occurred in 32.9% of mastectomies with principally skin or nipple-areola-complex suffering or necrosis, hematomas and infections. A predictive score was determined to evaluate risk of complications before surgery. Conclusion: Mastectomy with IBR seems to be a safe technique with an acceptable complication rate which is increased by tobacco use, high breast cup-size and IBR-type. Highlights: Mastectomy with immediate breast to determined immediate surgical results. More Nipple Sparing Mastectomy performed during the 2 last years. More Latissimus dorsi-flap performed for high BMI, high breast cup-size, after radiotherapy.